Analisis Pengaruh Peserta Didik, Pendidikan, dan Lingkungan terhadap Efektivitas Sistem Pembelajaran Daring dan Luring pada masa pandemi COVID-19 (Studi Kasus: Peserta Didik SMK Bhakti Anindya Kota Tangerang) - Jofy Eljabar Ukur; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The emergence of the Covid-19 pandemic in Indonesia has had a major impact on Indonesia, especially in the education system. The impact of the Covid-19 that occurred requires schools in Indonesia, especially SMK Bhakti Anindya to change their learning system from an offline learning system to an online one. The change in the teaching system from offline learning to online learning carried out by schools certainly triggers many problems. In the online learning method, students are required to study independently. It's because online learning is student-centered, so students must have an attitude of responsibility and autonomy in learning. In addition, from the educator side, online learning also has its own challenges. Separate learning between students and teachers causes teachers to not be able to monitor student learning processes directly like what they did before in offline learning. In this study, the authors examine how the influence of students, educators and the environment on the effectiveness of learning methods using online and offline methods at Bhakti Anindya Vocational School, Tangerang City. This research was conducted in several ways, including conducting observations, interviews, and distributing questionnaires to collect prime data. This study uses a random sampling technique in the data collection process with the number of respondents 30 students from class XI Multimedia SMK Bhakti Anindya. For data processing, this research uses a partial test (t-test), coefficient of determination test, product-moment correlation test, and simple linear regression test. After processing the data, this study obtained the following results (1) there is a partial effect between online learning media on students with a value of 7,787 > 2,048 and a significance value of 0.000 < 0.05 (2) there is a partial influence between online learning media on educators with a value of 15.273 > 2.048 and a significance value of 0.000 < 0.05 (3) there is a partial effect between offline learning media on students with a value of 8.991 > 2.048 and a significance value of 0.000 < 0.05 (4) there is no effect partial between offline learning media and educators with a value of -0.404 > 2.048 and a significance value of 0.690 <0.05.